2017
DOI: 10.1248/bpb.b17-00117
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Endothelial Barrier Permeability by Mitragynine

Abstract: Persistent inhalation of mitragynine (MG), a major alkaloid in the leaves of Mitragyna speciosa, causes various systemic adverse effects such as seizure, diarrhea and arthralgias, but its toxicity to endothelial cells and effects on barrier function of the cells are poorly understood. In this study, we compared toxicities of MG and mitraphylline, another constituent of the leaves, against human aortic endothelial (HAE), bronchial BEAS-2B, neuronal SK-N-SH, hepatic HepG2, kidney HEK293, gastric MKN45, colon DLD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
(21 reference statements)
0
7
0
Order By: Relevance
“…The decrease in tightness of the tight junction was not observed in cells pre-treated with ROS inhibitor, while ROS generators made it worse. This indicates the involvement of ROS in the disruption of tight junction integrity of the human aortic endothelial cells upon exposure to mitragynine ( Matsunaga et al, 2017 ).…”
Section: Interactions Of Kratom Alkaloids With Cellular Barriersmentioning
confidence: 90%
See 2 more Smart Citations
“…The decrease in tightness of the tight junction was not observed in cells pre-treated with ROS inhibitor, while ROS generators made it worse. This indicates the involvement of ROS in the disruption of tight junction integrity of the human aortic endothelial cells upon exposure to mitragynine ( Matsunaga et al, 2017 ).…”
Section: Interactions Of Kratom Alkaloids With Cellular Barriersmentioning
confidence: 90%
“…In vitro cell-based models of physiological barriers not only are great tools to investigate mechanisms of permeability but can also be used to determine the effects of exposure to compounds on the structure and function of the barriers. Exposure to mitragynine at 40 and 60 μM for 48 h reduced the viability of human aortic endothelial cells, which was linked to an increase in intracellular reactive oxygen species (ROS) production, leading to caspase-3 activation, DNA fragmentation, and apoptosis ( Matsunaga et al, 2017 ). The LC 50 determined was 43.1 μM.…”
Section: Interactions Of Kratom Alkaloids With Cellular Barriersmentioning
confidence: 99%
See 1 more Smart Citation
“…Further in-depth review revealed that mitragynine causes apoptotic cell death by releasing oxygen free radicals and also enhances endothelial barrier permeability. These mechanisms are thought to play a major role in the pathogenesis of ARDS [ 16 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Hyperpermeability is an important change associated with vascular dysfunction in neovascular diseases [ 42 ]. The paracellular permeability of the endothelium depends on the integrity of protein complexes involved in the inter-endothelial junctions [ 43 ]. ZO-1 and occludin are indispensable components of tight junctions regulated by pro-inflammatory cytokines and growth factors [ 44 49 ].…”
Section: Discussionmentioning
confidence: 99%